TRADISI MEGALITIK PADA RITUAL KEKERIK DI KALANGAN MASYARAKAT TENGGER - Putri Novita Taniardi (Balai Arkeologi Yogyakarta, 2013)
The Kekerik ritual has been conducted to celebrate 40 days baby delivery. The ritual is conducted by dukun, a ceremonial leader in Tengger society. This ritual is held to avoid some bad influences from evil spirits arounds. The baby who had this ritual means accepted by Tengger society and start a new life as a holy baby. This kekerik ritual shows megalithic tradition, which is the ancestor spirits is invited to bless the host and also some offerings is made to be presented for the ancestor spirits. The study that conducted in Keduwung village, Puspo district, Pasuruan Regency, East Java Province showed that kekerik ritual reflects megalithic tradition in a Tengger society. This condition is interesting because Tengger people has been known as Hinduneese. The study that define the relation between megalithic tradition and kekerik ritual is applying ethnoarchaeology approach, especially cultural sustainability which assumes that megalithic tradition in Tengger community is related to the past.